2017
DOI: 10.18632/oncotarget.17567
|View full text |Cite
|
Sign up to set email alerts
|

ROS enhance angiogenic properties via regulation of NRF2 in tumor endothelial cells

Abstract: Reactive oxygen species (ROS) are unstable molecules that activate oxidative stress. Because of the insufficient blood flow in tumors, the tumor microenvironment is often exposed to hypoxic condition and nutrient deprivation, which induces ROS accumulation. We isolated tumor endothelial cells (TECs) and found that they have various abnormalities, although the underlying mechanisms are not fully understood. Here we showed that ROS were accumulated in tumor blood vessels and ROS enhanced TEC migration with upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…A low degree of oxidative stress is thought to promote proper EC function and maintain the quiescent phenotype of ECs. In contrast, deregulated ROS levels in ECs promote angiogenesis and may become toxic [32].…”
Section: Autophagy In Ecsmentioning
confidence: 99%
“…A low degree of oxidative stress is thought to promote proper EC function and maintain the quiescent phenotype of ECs. In contrast, deregulated ROS levels in ECs promote angiogenesis and may become toxic [32].…”
Section: Autophagy In Ecsmentioning
confidence: 99%
“…Many studies have shown that ROS can activate Nrf2. 27,28 Therefore, our data strongly suggest that the imbalance of Nrf2-dependent redox in cardiomyocytes activated by NOX4-generated ROS is an important cause of myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 71%
“…The expression of Nrf2 is critical for cell survival and vitality during oxidative process in vivo and in vitro. Hojo et al () discovered that excessive ROS could inhibit the expression of Nrf2 to promote the formation of tumor endothelial cells. Nrf2‐deficient mice were reported with the trend to develop the severe hemolysis due to reduced antioxidant capacity (J. M. Lee, Chan, Kan, & Johnson, ).…”
Section: Discussionmentioning
confidence: 99%